Advances and challenges in cancer immunotherapy: mechanisms, clinical applications, and future directions - Vatsavai, Neeharika; Kaur Bhinder, Sumeet; Shaik, Rahaman; Mahira, Shaheen; Kapoor, Shruti; Ali, Md Shadab; Verma, Deepak; Singh, Jay; Badavenkatappa Gari, Sreelakshmi; Upadhyay, Prabhat; Meshkovska, Yeva; Godugu, Chandraiah; et al. (Frontiers in Pharmacology, 2025)
Cancer is a major threat to public health today, particularly due to the emergence of drug resistance and disease re-emergence post-traditional treatment. Regulatory T cells (Tregs) support cancer progression through their immunosuppressive mechanisms expressing co-inhibitory molecules like programmed cell death-1 (PD-1), cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), T cell immunoglobin-3 (TIM-3), and T-cell immunoglobin and ITIM domain (TIGIT), that suppress T-cell activation and allow tumor cells to grow uncontrollably. Emerging cancer immunotherapeutic strategies targeting these checkpoints inhibit tumor-immune escape and impede cancer progression. This review highlights the mechanistic effects of these drugs and enumerates various critical combinatorial strategies that can be utilized for effective cancer treatment.